Plant-insect relationships - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Host-plant selection by phytophagous insects by E A Bernays and R F Chapman 1994 312pp price UKL 22.95 Pbk ISBN 0 412 03131 0 Chapman and Hall 2-6 Boundary Row London SE1 8HN, UK